2012
DOI: 10.1186/1471-2164-13-407
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics among Saccharomyces cerevisiae × Saccharomyces kudriavzevii natural hybrid strains isolated from wine and beer reveals different origins

Abstract: BackgroundInterspecific hybrids between S. cerevisiae × S. kudriavzevii have frequently been detected in wine and beer fermentations. Significant physiological differences among parental and hybrid strains under different stress conditions have been evidenced. In this study, we used comparative genome hybridization analysis to evaluate the genome composition of different S. cerevisiae × S. kudriavzevii natural hybrids isolated from wine and beer fermentations to infer their evolutionary origins and to figure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 43 publications
2
98
1
1
Order By: Relevance
“…Interestingly, a high level of genomic diversity was found among these hybrids, despite a general reduction of the S. kudriavzevii genome fraction in most of them. A subsequent analysis of other S. cerevisiae-S. kudriavzevii hybrids from wine and beer confirmed the multiple patterns of chromosomal composition, despite the conservation of a common set of S. kudriavzevii genes possibly associated with cold adaptation (165). From the chromosomal rearrangements observed in hybrid genomes, it was concluded that multiple hybridizations took place, involving haploid and diploid parental strains.…”
Section: Molecular Analysis Of Wine Yeast Genomesmentioning
confidence: 75%
“…Interestingly, a high level of genomic diversity was found among these hybrids, despite a general reduction of the S. kudriavzevii genome fraction in most of them. A subsequent analysis of other S. cerevisiae-S. kudriavzevii hybrids from wine and beer confirmed the multiple patterns of chromosomal composition, despite the conservation of a common set of S. kudriavzevii genes possibly associated with cold adaptation (165). From the chromosomal rearrangements observed in hybrid genomes, it was concluded that multiple hybridizations took place, involving haploid and diploid parental strains.…”
Section: Molecular Analysis Of Wine Yeast Genomesmentioning
confidence: 75%
“…Also in Saccharomyces, interspecific hybrids that are allotriploid have been found. These hybrids have been isolated from cold winemaking and brewing environments, where it is suggested that the allotriploid hybrids have a selective advantage over their parents (67,68). So far, no other data on the ploidy level of B. bruxellensis strains isolated from other niches, such as beer, are available.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have investigated the fermentation characteristics of hybrids of these two yeasts and compared them with those of their parents 20 . S. kudriavzevii is more cryotolerant than S. cerevisiae, growing well at temperatures below the range that supports growth of S. cerevisiae 21 .…”
Section: Key Themesmentioning
confidence: 99%